Building your own games: A platform for authoring digital games - Rodrigues, Kamila; Darin, Ticianne; Neris, Vânia (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
End-User Development (EUD) solutions is a resource that empowers professionals from different domains to create their tools. However, the design of this type of solution must be well-thought-out so that such professionals can interact with the solution, creating your applications in a simple and intuitive way, without the presence of an IT specialist. Game design and development brings with it the inherent challenges of the media type. When creating a solution to make authoring viable, you should use holistic approaches that bring the target user to the focus of the process. This paper presents a platform for digital authoring games, named RUFUS, created with the precepts of EUD, Organizational Semiotics, and Participatory Design. The platform offers a guided walkthrough for professionals to create their own games. A previous evaluation pointed to the tool's advantages, but also revealed aspects that the tool should improve, such as help and documentation.